Switching Axial Progenitors from Producing Trunk to Tail Tissues in Vertebrate Embryos - Jurberg, Arnon Dias (2016)
The vertebrate body is made by progressive addition of new tissue from progenitors at the posterior embryonic end. Axial extension involves different mechanisms that produce internal organs in the trunk but not in the tail. We show that Gdf11 signaling is a major coordinator of the trunk-to-tail transition. Without Gdf11 signaling, the switch from trunk to tail is significantly delayed, and its premature activation brings the hindlimbs and cloaca next to the forelimbs, leaving extremely short trunks. Gdf11 activity includes activation of Isl1 to promote formation of the hindlimbs and cloaca-associated mesoderm as the most posterior derivatives of lateral mesoderm progenitors. Gdf11 also coordinates reallocation of bipotent neuromesodermal progenitors from the anterior primitive streak to the tail bud, in part by reducing the retinoic acid available to the progenitors. Our findings provide a perspective to understand the evolution of the vertebrate body plan.